¿Imposibilidad o error estratégico? La poca competitividad electoral de los partidos políticos peruanos en la última década - Puémape, Félix (2013)
Usually, the explanations about the little electoral competitiveness of peruvian political parties have emphasized the unlikelihood that this situation could be reversed. However, when each case is analyzed carefully, we can see that groups like APRA and the Fujimorista Movement have developed some features beyond their leaders which, in certain situations, have provide them a little more electoral competitiveness than others parties, such as the Popular Christian Party (PPC). From this point, the following article argues that this difference in the competitiveness of the peruvian parties is basically for the type of strategies that they have been implemented. While some of them have seen in the permanent positioning a way to be more competitive in the medium term, others have believed that the competitiveness is achieved more quickly when political parties reduce their intervention in political debates. In that sense, this article tested an actor-center explanation to understand the little competitiveness of peruvian parties and also will risk a less pessimistic view of their future.